(untitled) (Medical Forum Monthly, 2024)
Objective: To determine the frequency of depression among patients of diabetes mellitus attending diabetes clinic. Study Design: Descriptive / cross sectional study Place and Duration of Study: This study was conducted at Department of Medicines, Ch. Rehmat Ali Memorial Teaching Hospital, Lahore and Khairpur Medical College Hospital, Khairpur from 1st April 2016 to 30th September 2016. Materials and Methods: A total of 196 patients with diabetes mellitus of age 18-65 years of either gender were included. Patients with history of mood disorders, psychotic disorders, anxiety disorders prior to onset of DM, other chronic disease and any drug addiction were excluded. The demographic information like name, age, sex, socioeconomic status and duration of disease was noted in each patient. All patients were assessed by single psychiatrist, using DSM-IV criteria for Depression (Yes/No). Results: Mean age was 53.35±6.71 years in our study with majority of the patients 97 (49.49%) were between 51 to 65 years of age. Out of the 196 patients, 89 (45.41%) were male and 107 (54.59%) were females. Majority of patients 54.41% belonged to upper socioeconomic status. Depression was found in 47 (23.98%) patients, whereas there were 149 (76.02%) patients having no depression. Conclusion: This study concluded that prevalence of depression in type 2 diabetic patients was very high. So, proper evaluation of the co-morbid depression in diabetics should be done.